2012
DOI: 10.2174/138955712798995020
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Effects of Phytoestrogens and Alternative Menopausal Hormone Therapy in Cardiovascular Disease

Abstract: Phytoestrogens are estrogenic compounds of plant origin classified into different groups including isoflavones, lignans, coumestans and stilbenes. Isoflavones such as genistein and daidzein are the most studied and most potent phytoestrogens, and are found mainly in soy based foods. The effects of phytoestrogens are partly mediated via estrogen receptors (ERs): ERα, ERβ and possibly GPER. The interaction of phytoestrogens with ERs is thought to induce both genomic and non-genomic effects in many tissues includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 242 publications
(244 reference statements)
5
88
0
6
Order By: Relevance
“…Due to the disputable effects of the conventional hormone replacement therapy (Rossouw et al, 2002), plant-derived supplements are of increasing interest as useful in alleviation of menopausal symptoms. Phytoestrogens may also delay the progression of atherosclerosis by reduction of pathological changes in the cardiovascular system, such as alterations in the lipid profile, inflammatory processes, and oxidative stress (Gencel et al, 2011). Isoflavonoid phytoestrogens significantly contribute to medicinal properties of Trifolium plants, however, it should be emphasized that in addition to isoflavones, clovers synthesize a wide range of other bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the disputable effects of the conventional hormone replacement therapy (Rossouw et al, 2002), plant-derived supplements are of increasing interest as useful in alleviation of menopausal symptoms. Phytoestrogens may also delay the progression of atherosclerosis by reduction of pathological changes in the cardiovascular system, such as alterations in the lipid profile, inflammatory processes, and oxidative stress (Gencel et al, 2011). Isoflavonoid phytoestrogens significantly contribute to medicinal properties of Trifolium plants, however, it should be emphasized that in addition to isoflavones, clovers synthesize a wide range of other bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%
“…of cancer and neurodegenerative diseases (37). It has been reported that genistein enhances the induction of apoptosis by chemotherapeutic agents in several types of cancer cells (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Kémiai szerkezetük alapján négy csoportba oszthatjuk őket (1. táblázat): izoflavonoidok, lignánok, kumesztá-nok, sztilbének [16].…”
Section: Fitoösztrogénekunclassified